Association between pro-inflammatory alleles and allergic phenotypes in Xhosa adolescents - Laurence, C.; van der Merwe, L.; Zhang, Guicheng; Le Souëf, P.; Levin, M. (Wiley InterScience (John Wiley and sons), 2018)
© 2018 EAACI and John Wiley and Sons A/S. Published by John Wiley and Sons Ltd. Background: Significant differences exist in the prevalence, spectrum, and severity of allergic diseases between developing and developed countries and between subpopulations within single countries. These discrepancies likely result from a complex interaction between genetic and environmental factors. However, the precise nature of the contribution of ethnicity to genetic differences in the predisposition to allergic disease is not yet fully understood. In particular, there is a paucity of literature regarding the genetic determinants of allergic disease in people of black African origin with little or no genetic admixture. Objective: We aimed to analyze associations between 27 single nucleotide polymorphisms (SNPs) and allergy phenotypes in the local Xhosa population. Methods: A convenience sample of 213 Xhosa teenagers was enrolled at a local high school. Phenotypic data were collected in the form of a symptom questionnaire, skin prick tests for common food and aeroallergens, total serum IgE, and IgE to Ascaris lumbricoides. In addition, genotyping was performed to establish the prevalence of putative pro-inflammatory alleles. Results: We demonstrated several significant associations between polymorphisms and allergy phenotypes. In particular, 2 polymorphisms in the IL-10 gene (IL10 -592A > C and IL10 -1082A > G) and 1 in the IL-4 gene (IL4 -589C > T) showed multiple associations with allergic sensitization and asthma phenotypes. Other polymorphisms, across a multitude of genes with discrepant fu nctions, showed less consistent associations. Conclusion: This study represents an important first step in genotype/phenotype association in this population. Further research is required to confirm or refute our findings.